STRANgE, integrated physical–biological–mechanical system for recovery in of the “oil spill” in Antarctic environment - Cappello, Simone; Mancini, Giuseppe; Azzaro, Maurizio; Bottino, Francesco; Luciano, Antonella; Mamo, Antonino; Yakimov, Michail; PISTONE, Alessandro; GENOVESE, LUCREZIA; IANNAZZO, Daniela; NERI, Giovanni; GALVAGNO, Signorino; et al. (Reviews in Environmental Science and Bio/Technology, 2014)
Throughout the last century the increasing human activities in Antarctic region, particularly research expeditions, fishing, and tourism amplified the risk of oils spills at these high latitudes of the meridional hemisphere. A number of studies have been focused on chronic hydrocarbon contamination near Antarctic research stations revealing the presence and persistence of these human-derived contaminants. Marine ship-source oil spills in Antarctic region can have significant impacts on the marine environment. The key factors to effectively fight oil spills are a careful selection and proper use of the equipment and materials best suited to the critical local conditions. Despite the significant advances in the field of environmental recovery after an ‘‘oil spill’’ episode, research has recently shown that the usual techniques are often less effective than expected. This issue become much more relevant in the Antarctic case, not only for the incomparable environmental value of the Antarctic region but also for the extreme environmental conditions and the great distances from properly equipped centers, that make unfeasible sending naval vessels. Scope of the STRANgE Project is the preliminary design of a prototype floating platform, parachutable by plane, able to intervene as quickly as possible for the containment, removal and treatment/ storage of the oil slick. New sorbent nanostructured materials and specialized Antarctic bacteria applications constitute the main innovations of this Project.